If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -37 = 6(3 + 2m) Reorder the terms: -37 + m = 6(3 + 2m) -37 + m = (3 * 6 + 2m * 6) -37 + m = (18 + 12m) Solving -37 + m = 18 + 12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12m' to each side of the equation. -37 + m + -12m = 18 + 12m + -12m Combine like terms: m + -12m = -11m -37 + -11m = 18 + 12m + -12m Combine like terms: 12m + -12m = 0 -37 + -11m = 18 + 0 -37 + -11m = 18 Add '37' to each side of the equation. -37 + 37 + -11m = 18 + 37 Combine like terms: -37 + 37 = 0 0 + -11m = 18 + 37 -11m = 18 + 37 Combine like terms: 18 + 37 = 55 -11m = 55 Divide each side by '-11'. m = -5 Simplifying m = -5
| -1-m=-2 | | 45(15)+200=x | | c=38.56+0.25x | | 4x+31x-6=7(5x+9) | | -12=6.4+m | | 600m+.05=900m+.01 | | 48+(5x+2)=180 | | x/7-3 | | -34-11x=20-8x | | 6g-3=15g | | 5x+4=-8+3+16 | | w-2a=nw | | 5n+6=7n-2 | | 0=5.75+0.89m | | 1/2(6-10x)+4=1/4(12x-20) | | W-2.45=3.1 | | 4(a-5)=-28 | | -4n(2n-3)=12-8n | | 6x-2x-4=-2x-2 | | 90+(7x-8)=180 | | -(-5-6x)=4(3+5x) | | -7x/5=49 | | -3+x/2=-6 | | 3/7=5/6+y | | 4z+4=2z+7 | | 2x+9=3y | | 8-1/3x=9 | | H+21=-51 | | X/9+12=9 | | 65+x-5+x=180 | | 42/1/2 | | t-7d=nt |